KARAKTERISTIK PERJALANAN DAN MODA SEPEDA MOTOR DI KOTA BANDUNG - Effendi, Bekti Albar; Joewono, Tri Basuki (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Motorcycle choice might be influenced by travel characteristics. The purpose of this study is to analyze relationship between motorcycle characteristics and travel characteristics of motorcyclist. The data used in this study are primary data gathered from questionnaire distribution to motorcyclist in the City of Bandung. The results show that motorcycle characteristics distribution by the type and purchase status of motorcycle is different. Type of motorcycle has a weak relationship with travel characteristics. The capacity of the bike also has weak relationship with trip distance and trip frequency per day. Differently with motorcycle purchase status, it isn’t having a significant relationship with travel characteristics, except trip distance.